Models of technical system maintenance management - Epler, Igor Joso (Vojnotehnički glasnik / Military Technical Courier, 2013)
Existing models of management maintenance of tehnical systems are provideing reqiired reliability and availability of the system, preferably with as litlle cost. New cncepts, which are increasingly applied in all areas of life, are based on risk. Such an approach is possible and desirable in the field of theory and engineering of maintenance of tehnical systems and military tehnical systems. In this paper, the conceptual definitions of tehnical systems maintenance, maintenance management models and strategies are given. Then an overview of strategies and models of maintenance of tehnical systems, their shematic views and mutual comparisons and trends in the management of maintenance of tehnical systems, which could lead to the application may be able to achieve savings in maintenance, both tehnical and military tehnical systems.